BIPAP protocol usage in patients admitted to the Internal Medicine unit - Óscar Bautista Villaécija; Fernando Campaña Castillo (Fundación para el Desarrollo de la Enfermería, 2013)
The use of noninvasive mechanical ventilation equipment becomes more common in internal medicine units. Due to its indications, such as severe respiratory failure, or hypoxemic respiratory failure, it means a great help in these units. Within the multidisciplinary team, the medical staff is responsible for the prescription and programming of the device parameters, and the nursing staff handles such equipment and provides care to the patients requiring noninvasive mechanical ventilation.The objective of this protocol is to show in a clear and simple way, the noninvasive mechanical ventilation system, as well as its advantages and complications, and the nursing diagnoses that should be considered.